2009
DOI: 10.1210/jc.2008-1400
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl-Peptidase-IV Inhibition Augments Postprandial Lipid Mobilization and Oxidation in Type 2 Diabetic Patients

Abstract: Our study is the first to suggest that DPP-4 inhibition augments postprandial lipid mobilization and oxidation. The response may be explained by sympathetic activation rather than a direct effect on metabolic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 32 publications
7
54
0
3
Order By: Relevance
“…In an interesting paper, Boschmann et al . have demonstrated that vildagliptin increased post-prandial lipid mobilization and oxidation, in T2DM patients, effects mainly attributable to the activation of the adrenergic system, rather than to a peculiar metabolic action [30]. In a similar mouse model, vildagliptin administration was able not only to ameliorate the insulin resistance condition, but also to determine cardioprotection.…”
Section: Potential Positive Indirect Effects On Cardiovascular Functionmentioning
confidence: 99%
“…In an interesting paper, Boschmann et al . have demonstrated that vildagliptin increased post-prandial lipid mobilization and oxidation, in T2DM patients, effects mainly attributable to the activation of the adrenergic system, rather than to a peculiar metabolic action [30]. In a similar mouse model, vildagliptin administration was able not only to ameliorate the insulin resistance condition, but also to determine cardioprotection.…”
Section: Potential Positive Indirect Effects On Cardiovascular Functionmentioning
confidence: 99%
“…Было установлено, что вилдаглиптин ингибирует абсорбцию триглицеридов из кишечника, снижает липолиз и со-держание триглицеридов в печени, а также увеличивает уровень норэпинефрина, что также способствует расще-плению жиров (рис. 3) [32,33,34]. Ингибиторы ДПП-4 представляют собой класс препаратов, способных обе-спечить дополнительные клинические преимущества в управлении СД2 у пациентов с избыточной массой тела и ожирением.…”
Section: сахароснижающие препараты нейтральные в отношении набора маunclassified
“…Some studies have shown that the DPP‐4 inhibitors linagliptin and vildagliptin do not pass the BBB38, 39. However, other studies have suggested that an increased plasma level of GLP‐1 or inhibition of DPP‐4, enhance transport of GLP‐1 across the BBB18, 40.…”
Section: Biology Of Incretin Hormones In Peripheral Organs and The Brainmentioning
confidence: 99%